Physico-Chemical Studies on Polyvinyl Alcohol in Aqueous Media (Global Journal of Science Frontier Research, 2017)
Density, viscosity and speed of sound of aqueous solution of polyvinyl alcohol of different concentration range from 0.3% to 1% have been measured using ultrasonic interferometer at 1MHz frequency in temperature range 30 0 C-65 0 C. Using these values different acoustical parameters like adiabatic compressibility, acoustic impedance and have been calculated.
Keywords: ultrasonic velocity; adiabatic compressibility; acoustic impedance